Proposals for a systemic educational approach towards a sustainable society: Ecological transition, gender and intimate citizenship - Eleonora Bonvini; Silvia Demozzi; Marta Ilardo (Encyclopaideia)
The neoliberal model challenges ecological and social transitions, perpetuating socio-cultural norms that shape, capitalise on, and regulate subjectivities. Based on these premises, this paper considers and discusses Goals 4 and 5 of the 2030 Agenda, aiming to critically address the main issues linked to these objectives. First, we suggest a critical approach to deconstruct and connect dominant paradigms and social and political issues related to these SDGs. In this context, we consider the systemic-ecological thought of Bateson and the concept of “intimate citizenship” offered by Plummer. Based on these theoretical frameworks, we propose a pedagogical trajectory to investigate and understand reality systemically and ecologically. Finally, we identify the Comprehensive Sexuality Education (CSE) as an educational practice to address the complexity of current challenges.